(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Cascading and distorted taxes on the production of goods and services characterize indirecttaxation, which reduces efficiency and retards economic development. In the current setup, there are aplethora of taxes, but only a small fraction is collected by the federal government (the Center). Toeliminate this tax complexity and reduce the cost on taxpayers, a streamlined tax like a goods andservices tax is required (GST). The purpose of this research is to examine how the Goods and ServicesTax has affected business in India. In order to be considered effective, a social plan or programme mustenhance the welfare state, reduce social inequality, and contribute to the growth of the nation. TheGoods and Services Tax will significantly alter the current framework of India’s tax system, and thisarticle provides a conception of such changes. The Goods and Services Tax (GST) is unique amongindirect taxes in that it affects every economic and industrial sector, as far as I am aware. As a federaldemocratic nation, India implemented the GST simultaneously at the federal and state levels as CGSTand SGST. This article set out to do just that, with an emphasis on India and its implementation of Goodsand Services Tax (GST). The early effects on the economy and the difficulties the government facedimplementing it are then discussed.